2021
DOI: 10.1002/ls.1537
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical properties of tribofilms formed by the interaction of ashless dithiophosphate anti‐wear additives

Abstract: Physiochemical properties of tribofilms generated from octadecylthioperoxydiphosphate (SSC18) and octadecylphosphorofluoridothioate (PFC18) were compared with zinc dialkyl dithiophosphates (ZDDP) in this study. PFC18 and SSC18 were chemically synthesised and mixed in mineral base oil to prepare test oil formulations. Additionally, PFC18 and SSC18 were mixed at different concentrations and evaluated for their compatibility and tribological performance using high frequency reciprocating rig (HFRR) tribometer. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…XANES P L-edge indicated that the tribofilms formed with P_DEHP(350P/700P)+SB contains relatively longer chainlength phosphates in the near-surface region than the bulk of the tribofilms. Earlier studies have shown that longer chain phosphates yield better tribological properties and are generally considered to be more beneficial (Bancroft et al, 1997;Mosey et al, 2006;Sharma et al, 2015;Vyavhare et al, 2021a,b,c, Vyavhare et al, 2021. Additionally, XANES results indicated that the chain length of phosphates increases with the rubbing time.…”
Section: Tribofilm Formation and Anti-wear Mechanismmentioning
confidence: 99%
“…XANES P L-edge indicated that the tribofilms formed with P_DEHP(350P/700P)+SB contains relatively longer chainlength phosphates in the near-surface region than the bulk of the tribofilms. Earlier studies have shown that longer chain phosphates yield better tribological properties and are generally considered to be more beneficial (Bancroft et al, 1997;Mosey et al, 2006;Sharma et al, 2015;Vyavhare et al, 2021a,b,c, Vyavhare et al, 2021. Additionally, XANES results indicated that the chain length of phosphates increases with the rubbing time.…”
Section: Tribofilm Formation and Anti-wear Mechanismmentioning
confidence: 99%